Effects of blood flow restriction on internal and external training load metrics during acute and chronic short-term repeated-sprint training in team-sport athletes - Mckee, J. R.; De Marco, K.; Girard, O.; Peiffer, J. J.; Scott, B. R. (Journal of Sports Sciences, 2025)
This study examined internal, external training loads, internal:external ratios, and aerobic adaptations for acute and short-term chronic repeated-sprint training (RST) with blood flow restriction (BFR). Using randomised crossover (Experiment A) and between-subject (Experiment B) designs, 15 and 24 semi-professional Australian footballers completed two and nine RST sessions, respectively. Sessions comprised three sets of 5-7 × 5-second sprints and 25 seconds recovery, with continuous BFR (45% arterial occlusion pressure) or without (Non-BFR). Banister`s, Edwards`, Lucia`s training impulse, and session rating of perceived exertion training load (sRPETL) were calculated. External training loads were determined by total work done (TWD). Ventilatory threshold power outputs were assessed during a graded exercise test post-RST. Internal training loads were comparable between conditions, though BFR reduced (p < 0.02) TWD during acute (-4.9%) and short-term chronic (-10.0%) RST compared to Non-BFR. Furthermore, BFR increased (p = 0.049) the sRPETL:TWD ratio during short-term chronic (+14.8%), but not acute RST. First and second ventilatory threshold power outputs improved (+8.3% and + 4.2%, respectively) similarly for both groups following RST. Repeated exposure to progressively overloaded RST with BFR increases internal demands for a given workload, which may promote beneficial physiological adaptations compared to Non-BFR, though aerobic performance was not further enhanced.